Tafsir sebagai Ruang Ketiga: Hermeneutika Pesantren dan Ambivalensi Epistemik dalam Islam Poskolonial - Mohammad Nabil Iklil Mubarok; Zainuddin Syarif; Mohammad Thoha (Universitas Islam Negeri Sunan Kalijaga, 2026)
This study examines the epistemological construction of pesantren Qur’anic exegesis within a postcolonial framework by analyzing three contemporary works: Safīnah Kallā Saya‘lamūn, Hidayatul Qur’an, and Firdaus al-Na‘īm. The research addresses a persistent gap in scholarship that relegates pesantren exegesis to a marginal and non-innovative tradition, often overlooking its dynamic engagement with modern intellectual demands. Employing a qualitative interpretive method and drawing on Homi K. Bhabha’s postcolonial concepts of ambivalence, mimicry, and hybridity, this study explores how pesantren scholars negotiate between classical epistemic authority and contemporary academic expectations. The findings demonstrate that pesantren exegetes construct a hybrid form of knowledge through the selective integration of traditional authoritative frameworks with modern scholarly structures. This hybrid model highlights the agency of pesantren in shaping Qur’anic epistemology that is both contextually grounded and capable of challenging colonial and orientalist representations. The study argues that pesantren tafsir functions as an active participant in the global circulation of Qur’anic interpretation, offering alternative epistemic pathways that contribute significantly to the broader project of decolonizing Islamic studies.